HUMBLENESS AND HUMANITY: ANALYSIS OF THE CURRENT SCENARIO UNDER ISLAMIC PERSPECTIVES - Naseem Akhter, Serfraz Hussain Saeed, Talib Ali Awan, Muhammad Imran, Arshad Munir. (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Islam is an ideal religion; which Allah Almighty has chosen people. Islam shows harmony, concordance, equity, uniformity, fraternity, and humbleness. So that peace and harmony prevail in society. Humbleness is the best quality of Islam. The person who embraces humbleness has a fruitful existence in this world and the great beyond. Yet, it is our disaster that Islamic lessons are being disregarded with the passing minutes because of which the present individual has failed to remember virtues. At the point when we talk about the present society, conditions have deteriorated. The characteristics of humbleness, abstinence, patience, tolerance, and humanity are vanishing in each individual because of which incalculable disasters are emerging in the general public like oppression, murder, robbery, kidnapping, deprivation of rights, injustice, violence, corruption, and sedition. There is a need to not only awareness of Islamic teachings in society, but also to strictly follow them to improve the conditions of the society. The purpose of this article was to make clear this concept in the mind of individuals that humbleness is the best attribute. As well the attribute of humbleness was described in detail in the context of Islamic teachings and current society. So that this research work can make a positive message to improve moral values among people according to Islamic teachings.